Efficacy of ascorbic acid on processing characteristics and lipid oxidation of pre-rigor salted chicken breasts during vacuum refrigerated storage. (January 2020) - Ham, Youn-Kyung; Song, Dong-Heon; Ha, Jae-Ho; Park, Soo-Kyung; Kim, Yu-Ri; Chin, Koo Bok; Kim, Hyun-Wook
Abstract: The objective of this study was to evaluate the efficacy of ascorbic acid on processing characteristics and lipid oxidation of pre-rigor salted chicken breasts during 7 days of vacuum-packaged storage. Chicken breasts were deboned within 15 min after slaughter, immediately ground, and pre-rigor salted with 2% NaCl (w/w) or 2% NaCl (w/w) plus 500 ppm ascorbic acid. The pooled data from pre-rigor salted chicken breasts during storage showed significantly greater pH value, water-holding capacity, and protein solubility as compared to post-rigor salted chicken breasts. Moreover, the addition of 500 ppm ascorbic acid could not only effectively inhibit lipid oxidation, but also improve the brine uptake of pre-rigor salted chicken breasts ( P  < 0.05). The enhanced brine uptake when adding ascorbic acid may be related to the chelating effect of ascorbate anion on calcium ion, limiting the muscle contraction induced by rigor-mortis. The addition of ascorbic acid had no impact on total plate count of pre-rigor salted chicken breasts ( P  > 0.05). The results of this study suggest that pre-rigor salting with 500 ppm ascorbic acid could be effective in improving lipid oxidation stability during vacuum refrigerated storage, without negative impacts on processing characteristics. Highlights: Pre-rigor salted chicken breast was prepared with 500 ppm ascorbic acid. Ascorbic acid inhibited lipid oxidation of pre-rigor salted chicken breast. An improvement in brine uptake of pre-rigor salted chicken breast was found. Quality of pre-rigor salted chicken breast was maintained during storage.